2014
DOI: 10.7314/apjcp.2014.15.3.1211
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic Survey of Infantile Cancer in Iran based on the Data of the Largest Pediatric Cancer Referral Center (Ali-Asghar Children Hospital), 1996-2005

Abstract: Background: Cancer in infants younger than one year of age represents a unique problem with distinct epidemiological, clinical and genetic characteristics compared with older age groups. No report is yet available from Iran regarding epidemiological and survival rate of cancers diagnosed in this age group. Materials and Methods: The population under study comprised of patients which were diagnosed and admitted to Ali-Asghar hospital between years 1996-2005. In total, 287 infants were included in the retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 27 publications
0
12
1
Order By: Relevance
“…Another institution demonstrated that the top three incidence rate of tumors were RB (44%), leukemia (19%) and NB (10%). [21] Our result showed that RB accounted for 51.8% of all malignant solid tumors in infants, higher than previously reported. The possible reason was that our hospital is specialized in ophthalmology.…”
Section: Discussioncontrasting
confidence: 53%
“…Another institution demonstrated that the top three incidence rate of tumors were RB (44%), leukemia (19%) and NB (10%). [21] Our result showed that RB accounted for 51.8% of all malignant solid tumors in infants, higher than previously reported. The possible reason was that our hospital is specialized in ophthalmology.…”
Section: Discussioncontrasting
confidence: 53%
“…So, a specialized child hood cancer registry has been advocated (Mehdiabadi et al, 2014). Furthermore, this type of analysis shed light on the pattern of care and necessitates the identification of socio-demographic determinants responsible for treatment compliance in childhood cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the incidence of cancer in children differs from 48 to 70 per million children less than 15 years of age [3]. The incidence of childhood cancer in some developed countries, such as in United State, Ireland, Switzerland, and in Australia has reported with rates of 15.3, 13, 13.5, and 16 per 100,000 children, respectively, however in Asia the data are generally lower [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%